Analysis of Net Profit Margin, Return on Assets, and Earnings Per Share on Stock Prices in Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange - Dede Hertina; Herry Achmad Buchory; Yana Hendayana; Tasya Nafila; Mohamad Bayu Herdiawan Hidayat (Journal of Economics and Management, 2026)
This study examines the relationship between financial performance indicators—namely Net Profit Margin (NPM), Return on Assets (ROA), and Earnings per Share (EPS)—and the stock prices of Food and Beverage companies listed on the Indonesia Stock Exchange from 2018 to 2022. A quantitative research framework was implemented using descriptive and hypothesis-testing (verificative) methods. The research sample comprised 19 companies selected purposively from a population of 39 firms, generating 95 panel data observations. Prior to hypothesis testing, the data were subjected to classical assumption tests, followed by multiple linear regression analysis to evaluate the effects of the independent variables on stock prices. The results show that partially NPM and EPS have a positive and significant effect on stock prices, while ROA has a negative and insignificant effect. Simultaneously, the three independent variables significantly influence stock prices with a coefficient of determination (R²) of 81.4%, indicating that 81.4% of stock price variation can be explained by NPM, ROA, and EPS, while the remaining 18.6% is influenced by other factors outside the model. The findings imply that profitability indicators, particularly NPM and EPS, are important considerations for investors in evaluating stock performance within the Food and Beverage industry. This study contributes to strengthening empirical evidence regarding fundamental analysis in investment decision-making.